2002
DOI: 10.1074/jbc.m106588200
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Titration Calorimetry Reveals a Zinc Ion as an Atomic Switch in the Diadenosine Polyphosphates

Abstract: Diadenosine polyphosphates (diadenosine 5,5ٟ-P 1 ,P npolyphosphate (Ap n A)) are 5-5ٟ-phosphate-bridged dinucleosides that have been proposed to act as signaling molecules in a variety of biological systems. Isothermal titration calorimetry was used to measure the affinities of a variety of metal cations for ATP, diadenosine 5,5ٟ-P 1 ,P 3 -triphosphate (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 48 publications
1
19
3
Order By: Relevance
“…Taking into account the ability of zinc ions to increase the activity of AppCH 2 ppA due to formation of the complex with this agent [7], we decided to check the relation between this peculiarity of the polyphosphate and its action on the currents through the NMDA channels. For this purpose, we used a highaffinity chelator of divalent cations, ethylenediaminetetraacetic acid, EDTA [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the ability of zinc ions to increase the activity of AppCH 2 ppA due to formation of the complex with this agent [7], we decided to check the relation between this peculiarity of the polyphosphate and its action on the currents through the NMDA channels. For this purpose, we used a highaffinity chelator of divalent cations, ethylenediaminetetraacetic acid, EDTA [8].…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated recently that the conformation of AppCH 2 ppA, the analog of DAPPh, is modified due to the formation of its complex with zinc ions [7]. The high-affinity bond between the N7 atoms of the two adenine rings and the endergonic bond with the phosphate chain are involved in the binding of Zn 2+ with the AppCH 2 ppA molecule.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a novel role for Zn(II) in Ap 4 A physiology was proposed, consisting of a putative stabilization of the active conformation of the dinucleotide. This proposal was based on a particularly high binding constant for the Zn(II)-Ap 4 A complex at neutral pH (log K $ 7), obtained by isothermal titration calorimetry (ITC) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The ␣ phosphates are centered at −11.3 ppm and the ␤ phosphates at −23.0 ppm (referenced to external phosphoric acid standard). There are several reported NMR studies of Ap 4 A (Plateau et al, 1981;Kolodny and Collins, 1986;Westkaemper, 1987;Tanner et al, 2002). Plateau et al reported coupling constants of 2 J ␣␤ = 16.3 and 2 J ␤␤ = 13.7 Hz, measured at pH 7.8 with 5 mM MgCl 2 present, while Kolodny and Collins, working at pH 7.0, reported 2 J ␣␤ = 15.36 Hz, 4 J ␣␤ = 3.02 Hz, as well as an unexpectedly small coupling 2 J ␤␤ = 10.77 Hz between the two central ␤ phosphates, and a surprising six bond coupling 6 J ␣␣ = 5.73 Hz between the two ␣ phosphorus nuclei.…”
Section: Phosphorus-31 Nmr Characterizationmentioning
confidence: 99%